Structural Features and Digestibility of Corn Starch With Different Amylose Content - Lv, Xinxin; Hong, Yan; Zhou, Qiwei; Jiang, Chengchen (Frontiers in Nutrition, 2021)
In this study, the in vitro digestibility of corn starch with different amylose content was determined. The results showed that waxy corn starch (WCS) and corn starch (CS) have the highest digestibility, while high amylose corn starch (HACS) has a higher content of resistant starch (RS). Besides being related to amylose content, RS content is also closely related to particle shape, branched fine structure, molecular structure and semi-crystalline structure. HACS can maintain a complete particle structure after gelatinization and enzymolysis; differential scanning calorimetry showed a positive correlation between gelatinization enthalpy and RS content. As the amylose content increased, the content of fa (DP 6-12) decreased, while the content of fb2 (DP 25-36) and fb3 (DP ≥ 37) increased, which in-turn decreased the cluster polymer formed by short branch chains, and the formation of more hydrogen bonds between long chain branches improved starch stability. D, which characterizes the compactness of starch semi-crystalline structure, increased with the increase of RS content. HACS 60 with the highest RS content had a unique surface fractal structure between 7.41 < d (2π/q) < 10.58 nm, indicating that the dense structure is effective in maintaining the RS content.